2022
DOI: 10.21873/invivo.12850
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Deficiency and Vitamin D Receptor Genetic Variants With Coronary Artery Disease in Type 2 Diabetic Saudi Patients

Abstract: Background/Aim: Vitamin D deficiency accelerates the onset of type 2 diabetes mellitus (T2DM). Polymorphisms in the vitamin D receptor (VDR) have been linked to coronary artery disease (CAD). This study aimed to evaluate the association of vitamin D deficiency and VDR polymorphism with CAD in T2DM. Patients and Methods: A total of 150 adult male and female subjects, aged from 40 to 60 years, were divided into three groups, each with 50 subjects; control group, T2DM, and T2DM with CAD. Fasting blood glucose (FB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In T2DM, a decline in lipase activity compared to the insulin level leads to elevated TG and LDL-C levels, along with reduced HDL-C level [37]. Several studies have demon-strated the link between vitamin D and lipid profile in T2DM [38][39][40]. A recent meta-analysis has suggested that vitamin D does not exert significant effects on the levels of TC, LDL-C, and HDL-C in children and adolescents [41].…”
Section: Discussionmentioning
confidence: 99%
“…In T2DM, a decline in lipase activity compared to the insulin level leads to elevated TG and LDL-C levels, along with reduced HDL-C level [37]. Several studies have demon-strated the link between vitamin D and lipid profile in T2DM [38][39][40]. A recent meta-analysis has suggested that vitamin D does not exert significant effects on the levels of TC, LDL-C, and HDL-C in children and adolescents [41].…”
Section: Discussionmentioning
confidence: 99%
“… 10 More recently, we assessed the association of vitamin D deficiency with clinical presentation of COVID-19 and we found that inflammatory markers were negatively correlated with vitamin D level in COVID-19 patients. 11 Vitamin D deficiency was found to be prevalent in hyperglycaemic patients. 12 Accordingly, the current study aimed to evaluate the correlation between neutrophilia and inflammatory response markers and 25(OH)D level in hyperglycaemic COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between AIP have been reported with coronary artery disease, and diabetic foot and nephropathy in T2DM patients. [4][5][6] Negative correlations between AIP and vitamin D have also been found in Non-alcoholic fatty liver disease (NAFLD). 7 However, it is not known whether there is an association between vitamin D and AIP in T2DM.…”
Section: Introductionmentioning
confidence: 99%